Clinical and Etiological Profile of Ascites in the Departmental University Hospital of Porto-Novo - SEHONOU, JEAN; WANVOEGBE, FINANGNON ARMAND; KPOSSOU, ABOUDOU RAÏMI; AGBODANDE, KOUESSI ANTHELME; DOSSOU, JOSIANE; ATTINSOUNON, COSSI ANGELO (My University, 2017)
Aim: To determine the frequency, the clinical and etiological aspects of ascites in the Internal Medicine Division of the University Hospital of Porto-Novo. Methods: It was a cross-sectional study with a descriptive focus covering the period from January 16 to August 31, 2015. It covered patients hospitalized for ascites in Internal Medicine Department at the Departmental University Hospital of Porto-Novo during the study period. Data were collected on a survey sheet and entered by Excel and analyzed with SPSS. The Chi-square test was used for statistical analysis and a significance threshold of 5% was re-tained. Results: Of the 511 hospitalized patients during the study period, 61 (11.9%) had ascites. The mean age was 49.6 ± 13.6 years with extremes of 19 years and 80 years. There was a male predominance with a sex ratio of 2.05. Ascites were often type III (34 patients, 55.7%), or type II (22 patients, 36.1%). The frequent signs were hepatomegaly (65.6%), splenomegaly (45.9%), pelvic limb edema (44.3%), and abdominal collateral venous circulation (39.3%). The macroscopic appearance of the ascites fluid was dominated by citrin yel-low (82%), followed by hazy (11.5%). The hematic appearance was found in 6.5% of the cases. Hepatic cirrhosis was the most frequent etiology (34.4%) followed by overall heart failure (21.0%). Hepatocellular carcinoma was found in 16% of cases and nephrotic syndrome in 10% of cases. Conclusion: The etiological diversity of ascites, found in our study, imposes a careful clinical and paraclinical approach.
Keywords: Ascites; Etiology; Porto-Novo; Benin